Hubungan Persepsi Tentang Gambar Rokok dengan Perilaku Merokok Pada Remaja di Desa Tangguluri Kecamatan Asera Kabupaten Konawe Utara - Nurpaidal, Nurpaidal; Prasetya, Fikki (Jurnal Gizi Ilmiah, 2016)
Smoking is still one of the bad habits that are often done by Indonesians. This habit applies to almost all levels of society, both the lower and upper class economic communities. Similarly, smoking behavior in humans is the result of all kinds of experiences as well as, human interaction with the environment which is manifested in the form of knowledge, attitudes and actions. In addition, perception is a direct response (acceptance) of something. The process of a person knowing things through his five senses. The purpose of this study was to determine the relationship between perceptions of cigarette images and smoking behavior in adolescents. This research is a descriptive analytic study with a Cross Sectional Study approach. The population in this study were patients who smoked and did not smoke which were then selected to be a random sample, namely random sampling and met the specified sample criteria as many as 52 respondents. Collecting data by distributing questionnaires to respondents. The results of the study were processed using the Chi-Square test with a significance level of < 0.05. The results of the bivariate analysis showed that there was a relationship between perception and smoking behavior in adolescents in Tangguluri Village, Asera District, North Regency (p = 0.001). There is a need for a review by the government regarding more appropriate policies to create a better perception of the dangers of smoking